Targeting Metalloenzymes: The "Achilles' Heel" of Viruses and Parasites - Dimitrios Moianos; Georgia-Myrto Prifti; Maria Makri; Grigoris Zoidis (MDPI AG, 2023)
Metalloenzymes are central to the regulation of a wide range of essential viral and parasitic functions, including protein degradation, nucleic acid modification, and many others. Given the impact of infectious diseases on human health, inhibiting metalloenzymes offers an attractive approach to disease therapy. Metal-chelating agents have been expansively studied as antivirals and antiparasitics, resulting in important classes of metal-dependent enzyme inhibitors. This review provides the recent advances in targeting the metalloenzymes of viruses and parasites that impose a significant burden on global public health, including influenza A and B, hepatitis B and C, and human immunodeficiency viruses as well as Trypanosoma brucei and Trypanosoma cruzi.